The Educational Potential of Linking a Videodisc and an Expert System - Stensaas, Suzanne S. (1989)
A medical expert system, “Iliad” and a videodisc, “Slice of Life”, have been successfully interfaced. The expert system was designed to support medical students in their clinical diagnosis experience. The videodisc was also designed for undergraduate medical students. Both systems were developed independently and are presently being used as such in medical education. Modifications to the expert system were minimal and designed to support the linking of dictionary terms in a knowledge base to images and textual descriptions of videodisc images. These pictorial links enhance the informational capacity and utility of the expert system. It is hoped that images will increase retention, problem-solving ability, and enjoyment of the expert system.